Preparation method of high-transparency PVA optical thin film

PVA optical film is prepared by casting or scraping method, and is dried, annealed and surface treated, which solves the problems of complex preparation process, high cost and unsatisfactory transparency in the prior art, and achieves high transparency, good mechanical properties and Preparation of films with thermal stability.

CN119431846APending Publication Date: 2025-02-14SHANDONG SENGONG NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411733316.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The preparation process of the existing high-transparency PVA optical film is complex, costly, and the transparency is not ideal, and further improvement is needed.

Method used

The PVA solution is uniformly coated on the substrate by casting or scraping method, and after drying, annealing and surface treatment, a high transparency PVA optical film is obtained.

Benefits of technology

The preparation process is simplified, the cost is reduced, the transparency reaches more than 90%, the film has high tensile strength and good thermal stability, and is suitable for display technology, optical instruments and solar cells and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119431846A_ABST
    Figure CN119431846A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of optical thin films, and discloses a preparation method of a high-transparency PVA optical thin film, which comprises the following steps: preparing PVA powder, deionized water, a surfactant and a clean substrate, and using the deionized water as a solvent; the preparation method comprises the following steps: slowly adding PVA powder into deionized water, stirring while adding to fully dissolve the PVA powder, adding a surfactant, continuously stirring for a period of time to uniformly mix the solution, and heating the solution at a certain temperature for a period of time; uniformly coating a clean substrate with the prepared PVA solution by adopting a tape casting method or a blade coating method, putting the substrate coated with the PVA solution into a drying oven, drying for a period of time at a certain temperature to volatilize the solvent to form a PVA optical thin film, and removing the PVA optical thin film from the substrate after drying; the prepared PVA optical thin film is subjected to annealing treatment, the annealed PVA optical thin film is subjected to surface treatment, and the high-transparency PVA optical thin film is obtained; the film prepared by the method has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of optical films, and in particular to a method for preparing a high-transparency PVA optical film. Background Art

[0002] With the continuous progress and innovation of science and technology, the application scope of optical films has become more and more extensive in various fields, especially in the fields of display technology, optical instruments and solar cells. The application of optical films has become indispensable. In these applications, high-transparency PVA (polyvinyl alcohol) optical films have received extensive attention and attention due to their excellent optical properties, outstanding mechanical strength and good chemical stability.

[0003] However, despite the many advantages of high-transparency PVA optical films, there are still some problems and challenges in the current preparation process; first, the process of preparing high-transparency PVA optical films is relatively complicated, and multiple parameters need to be precisely controlled to ensure the quality and performance of the films; second, the preparation cost is relatively high, which is mainly due to the high cost of the required raw materials and equipment, as well as the need for fine operation and control during the preparation process; finally, although the transparency of PVA optical films is already relatively high, its transparency is still not ideal and needs to be further improved. Summary of the invention

[0004] The purpose of the present invention is to solve the above problems and to design a method for preparing a high-transparency PVA optical film.

[0005] The present invention provides a method for preparing a high-transparency PVA optical film, and the method for preparing the high-transparency PVA optical film comprises the following steps:

[0006] Step 1: prepare PVA powder, deionized water, surfactant and a clean substrate, and use deionized water as a solvent;

[0007] Step 2: slowly add PVA powder into deionized water, stirring while adding to fully dissolve the PVA powder, add surfactant, continue stirring for a period of time to mix the solution evenly, and heat the solution at a certain temperature for a period of time;

[0008] Step 3: uniformly coating the prepared PVA solution on a clean substrate by using a casting method or a doctor blade method, placing the substrate coated with the PVA solution in a drying oven, drying it at a certain temperature for a period of time to evaporate the solvent to form a PVA optical film, and peeling off the PVA optical film from the substrate after drying;

[0009] Step 4: annealing the prepared PVA optical film, and performing surface treatment on the annealed PVA optical film to obtain a high-transparency PVA optical film.

[0010] Optionally, in a first implementation of the present invention, the PVA powder in step 1 has a degree of polymerization of 1700-2000, a degree of alcoholysis of 99%-99.5%, a resistivity of the deionized water of greater than 18 MΩ·cm, and the surfactant is sodium dodecyl sulfate.

[0011] Optionally, in a second implementation of the present invention, the substrate in step 1 is a glass substrate or a stainless steel substrate, and when the substrate is a stainless steel substrate, the surface roughness is less than 0.1 μm.

[0012] Optionally, in the third implementation of the present invention, the specific process of step two is: use a reactor with a stirring paddle and a heating device to slowly add PVA powder into deionized water at a rate of 1-2 grams per minute, the stirring speed is 300-400r / min, and after adding the surfactant, continue stirring for 30-40 minutes. The solution heating temperature is 90-95°C and the heating time is 1-1.5 hours.

[0013] Optionally, in a fourth implementation of the present invention, when the casting method is adopted in step three, the flow rate of the casting machine is 5-10 ml / min, and when the scraper coating method is adopted, the scraper angle is 30-45 degrees.

[0014] Optionally, in a fifth implementation of the present invention, in step three, the substrate is wiped clean with anhydrous ethanol and dried before coating, and the substrate coated with the PVA solution is placed in a drying oven with a temperature of 80-85° C. and a drying time of 4-5 hours.

[0015] Optionally, in the sixth implementation of the present invention, the specific process of step four is: the prepared PVA optical film is annealed in an annealing furnace at a temperature of 120-130°C for 2-3 hours, and the annealed PVA optical film is surface treated with plasma treatment equipment or chemical vapor deposition equipment to obtain a high-transparency PVA optical film.

[0016] Optionally, in a seventh implementation of the present invention, a plasma treatment device is used to perform surface treatment on the annealed PVA optical film, and the plasma treatment device has a power of 100-200 W and a treatment time of 30-60 minutes.

[0017] Optionally, in an eighth implementation of the present invention, a chemical vapor deposition device is used to perform surface treatment on the annealed PVA optical film, the deposition temperature is 150-200° C., and the deposition time is 1-2 hours.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] 1. Simple preparation process: The preparation method adopted by the present invention is simple to operate, easy to control, and does not require complicated equipment and processes;

[0020] 2. Low cost: The raw materials used in the present invention are cheap, and the energy consumption in the preparation process is low, which reduces the production cost;

[0021] 3. High transparency: By optimizing the preparation process, such as strictly controlling the quality of raw materials, stirring and heating processes, and adopting appropriate post-processing methods, the prepared PVA optical film has extremely high transparency, and the transmittance can reach more than 90%; the film has high tensile strength and a certain elongation, within the range of 100-120MPa tensile strength and 10%-15% elongation, so that it can remain stable in various use environments and is not easy to break; in the thermal stability test, the film shows good stability within a certain temperature range, without obvious deformation, discoloration and other phenomena, and is suitable for applications in various temperature environments;

[0022] 4. Application prospects: Since the film has high transparency, good mechanical properties and thermal stability, it has broad application prospects in many fields such as display technology, optical instruments, solar cells, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the following detailed description of the preferred embodiment.The drawings are only for the purpose of illustrating the preferred embodiments and are not to be construed as limiting the invention.

[0024] Figure 1 A schematic flow chart of a method for preparing a high-transparency PVA optical film provided in an embodiment of the present invention. DETAILED DESCRIPTION

[0025] In order to better understand the technical solution of the present invention, the above content of the present invention is further described in detail below through specific implementation methods in the form of embodiments, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples. All technologies realized based on the above content of the present invention belong to the scope of the present invention.

[0026] For ease of understanding, the specific process of the embodiment of the present invention is described below. Figure 1 A schematic flow chart of a method for preparing a high-transparency PVA optical film provided by an embodiment of the present invention, the method specifically comprises the following steps:

[0027] Step 1: prepare PVA powder, deionized water, surfactant and a clean substrate, and use deionized water as a solvent;

[0028] Step 2: slowly add PVA powder into deionized water, stirring while adding to fully dissolve the PVA powder, add surfactant, continue stirring for a period of time to mix the solution evenly, and heat the solution at a certain temperature for a period of time;

[0029] Step 3: uniformly coating the prepared PVA solution on a clean substrate by using a casting method or a doctor blade method, placing the substrate coated with the PVA solution in a drying oven, drying it at a certain temperature for a period of time to evaporate the solvent to form a PVA optical film, and peeling off the PVA optical film from the substrate after drying;

[0030] Step 4: annealing the prepared PVA optical film, and performing surface treatment on the annealed PVA optical film to obtain a high-transparency PVA optical film.

[0031] In this embodiment, in step 1, the PVA powder has a degree of polymerization of 1700-2000, a degree of alcoholysis of 99%-99.5%, a resistivity of deionized water greater than 18 MΩ·cm, and a surfactant of sodium dodecyl sulfate; the substrate is a glass substrate or a stainless steel substrate, and when the substrate is a stainless steel substrate, the surface roughness is less than 0.1 μm.

[0032] In this embodiment, the specific process of step 2 is: using a reactor equipped with a stirring paddle and a heating device, the PVA powder is slowly added to the deionized water at a rate of 1-2 grams per minute, the stirring speed is 300-400r / min, and the stirring is continued for 30-40 minutes after the surfactant is added. The solution is heated to a temperature of 90-95°C and the heating time is 1-1.5 hours.

[0033] In this embodiment, when the casting method is adopted in step three, the flow rate of the casting machine is 5-10 ml / min, and when the scraper coating method is adopted, the scraper angle is 30-45 degrees; the substrate is wiped clean with anhydrous ethanol and dried before coating, and the substrate coated with the PVA solution is placed in a drying oven, the drying oven temperature is 80-85°C, and the drying time is 4-5 hours.

[0034] In this embodiment, the specific process of step four is: the prepared PVA optical film is annealed in an annealing furnace, the annealing temperature is 120-130°C, and the time is 2-3 hours, and the annealed PVA optical film is surface treated by plasma treatment equipment or chemical vapor deposition equipment to obtain a high-transparency PVA optical film; the annealed PVA optical film is surface treated by plasma treatment equipment, the plasma treatment equipment has a power of 100-200W, and the treatment time is 30-60 minutes; the annealed PVA optical film is surface treated by chemical vapor deposition equipment, the deposition temperature is 150-200°C, and the deposition time is 1-2 hours.

[0035] In this embodiment, the casting method is a method for preparing a thin film. The basic principle is to pass a polymer solution or melt through a specific mold (such as a slit mold) to form a uniform liquid film on a continuously moving support (such as a steel belt, a plastic belt or a glass substrate, etc.), and then solidify the liquid film by solvent evaporation (for a solution system) or cooling (for a melt system), and finally form a thin film. In the process of preparing a PVA optical film, the PVA solution is coated on the substrate by the casting method, and a thin film is obtained after the solvent evaporates; the PVA powder is dissolved in deionized water, a surfactant is added and stirred evenly, and heated to a suitable temperature to prepare a uniform PVA solution. The concentration, viscosity and other parameters of the solution need to be adjusted according to the thickness and performance of the desired film. The PVA solution is delivered to the slit mold through a metering pump. The solution flows out of the slit of the mold evenly and falls on the support body moving at a uniform speed to form a uniform liquid film. In this process, it is necessary to control parameters such as the flow rate of the solution, the moving speed of the support body, and the distance between the mold and the support body to ensure that the thickness and uniformity of the liquid film meet the requirements; the coated support body enters the drying system with the liquid film. In the drying system, the solvent is gradually evaporated through heating and ventilation. The drying temperature and time need to be adjusted according to factors such as the type of solvent, the concentration of the solution and the thickness of the film. For example, for PVA solution, the general drying temperature is 80-8 The temperature is about 5℃, and the drying time may take 4-5 hours, until the solvent is completely evaporated to form a solid PVA film; when the film is completely dry, it is peeled off from the support. For glass substrates, the film can be peeled off relatively easily; for steel belts or plastic belts, appropriate auxiliary tools or processes may be required, such as reducing the adhesion between the film and the support to ensure that the film is completely peeled off; the cast film method can produce films with uniform thickness, smooth surface and high transparency. In the continuous production process, as long as the equipment is debugged well, continuous coating and drying can be achieved, and a large number of films can be produced in a short time, which is suitable for large-scale industrial production.

[0036] Example 1.

[0037] Material preparation: electronic balance with an accuracy of 0.01g, clean workbench, 100g of PVA powder with a degree of polymerization of 1700 and a degree of alcoholysis of 99%, 1000ml of deionized water with a resistivity of 18.2MΩ·cm, 1g of sodium dodecyl sulfate, and a glass substrate with a size of 20cm×20cm and high flatness;

[0038] Solution preparation: PVA powder was added into deionized water at a rate of 1 gram per minute using a reactor equipped with a four-blade turbine stirring paddle and a heating device, with a stirring speed of 300 r / min. Stirring was continued for 30 minutes after adding the surfactant, and the solution was heated to 90°C for 1 hour.

[0039] Film preparation: The glass substrate was wiped clean with anhydrous ethanol and dried, and the prepared PVA solution was evenly coated on the clean substrate using a casting machine. The flow rate of the casting machine was controlled at 5 ml / min. The substrate coated with the PVA solution was placed in a drying oven. The temperature of the drying oven was set at 80°C and the drying time was 4 hours to form a PVA optical film. After drying, the PVA optical film was peeled off from the substrate;

[0040] Post-treatment: The prepared PVA optical film was annealed in an annealing furnace with the temperature set at 120°C for 2 hours. The annealed PVA optical film was surface treated with a plasma treatment device with the plasma treatment power set at 100W for 30 minutes to obtain a high-transparency PVA optical film.

[0041] Example 2.

[0042] Material preparation: electronic balance with an accuracy of 0.01g, clean workbench, 110g PVA powder with a degree of polymerization of 1800 and a degree of alcoholysis of 99.2%, 1100ml of deionized water with a resistivity of 18.5MΩ·cm, 1.2g of sodium dodecyl sulfate, and a stainless steel substrate with a size of 15cm×15cm and a surface roughness of 0.08μm;

[0043] Solution preparation: PVA powder was added into deionized water at a rate of 1.5 g / min using a reactor equipped with a four-blade turbine stirring paddle and a heating device, with a stirring speed of 350 r / min. Stirring was continued for 35 minutes after adding the surfactant, and the solution was heated to 92°C for 1.2 hours.

[0044] Film preparation: The glass substrate was wiped clean with anhydrous ethanol and dried, and the prepared PVA solution was evenly coated on the clean substrate using a scraper. The scraper angle of the scraper was adjusted to 35 degrees. The substrate coated with the PVA solution was placed in a drying oven. The temperature of the drying oven was set at 82°C. The drying time was 4.5 hours to form a PVA optical film. After drying, the PVA optical film was peeled off from the substrate.

[0045] Post-treatment: The prepared PVA optical film was annealed in an annealing furnace with the temperature set at 125°C for 2.5 hours. The annealed PVA optical film was surface treated using chemical vapor deposition equipment with the chemical vapor deposition temperature controlled at 160°C for 1.5 hours to obtain a high-transparency PVA optical film.

[0046] Example 3.

[0047] Material preparation: electronic balance with an accuracy of 0.01g, clean workbench, 120g of PVA powder with a degree of polymerization of 1900 and a degree of alcoholysis of 99.4%, 1100ml of deionized water with a resistivity of 18.8MΩ·cm, 1.4g of sodium dodecyl sulfate, and a glass substrate with a size of 25cm×25cm and high flatness;

[0048] Solution preparation: PVA powder was added into deionized water at a rate of 1.8 g / min using a reactor equipped with a four-blade turbine stirring paddle and a heating device, with a stirring speed of 380 r / min. Stirring was continued for 38 minutes after adding the surfactant, and the solution was heated to 94°C for 1.4 hours.

[0049] Film preparation: The glass substrate was wiped clean with anhydrous ethanol and dried, and the prepared PVA solution was evenly coated on the clean substrate using a casting machine. The flow rate of the casting machine was controlled at 8 ml / min. The substrate coated with the PVA solution was placed in a drying oven. The temperature of the drying oven was set at 84°C. The drying time was 4.8 hours to form a PVA optical film. After drying, the PVA optical film was peeled off from the substrate;

[0050] Post-treatment: The prepared PVA optical film was annealed in an annealing furnace with the temperature set at 128°C for 2.8 hours. The annealed PVA optical film was surface treated with a plasma treatment device with the plasma treatment power set at 150W for 45 minutes to obtain a high-transparency PVA optical film.

[0051] Example 4.

[0052] Material preparation: electronic balance with an accuracy of 0.01g, clean workbench, 130g PVA powder with a degree of polymerization of 2000 and a degree of alcoholysis of 99.5%, 1300ml of deionized water with a resistivity of 19MΩ·cm, 1.5g of sodium dodecyl sulfate, and a stainless steel substrate with a size of 18cm×18cm and a surface roughness of 0.07μm;

[0053] Solution preparation: PVA powder was added into deionized water at a rate of 2 g / min using a reactor equipped with a four-blade turbine stirring paddle and a heating device, with a stirring speed of 400 r / min. Stirring was continued for 40 minutes after adding the surfactant, and the solution was heated to 95°C for 1.5 hours.

[0054] Film preparation: The glass substrate was wiped clean with anhydrous ethanol and dried, and the prepared PVA solution was evenly coated on the clean substrate using a scraper. The scraper angle of the scraper was adjusted to 45 degrees. The substrate coated with the PVA solution was placed in a drying oven. The temperature of the drying oven was set at 85°C. The drying time was 5 hours to form a PVA optical film. After drying, the PVA optical film was peeled off from the substrate.

[0055] Post-treatment: The prepared PVA optical film was annealed in an annealing furnace with the temperature set at 130°C for 3 hours. The annealed PVA optical film was surface treated using chemical vapor deposition equipment with the chemical vapor deposition temperature controlled at 180°C for 1.8 hours to obtain a high-transparency PVA optical film.

[0056] Example 5.

[0057] Material preparation: electronic balance with an accuracy of 0.01g, clean workbench, 105g of PVA powder with a degree of polymerization of 1750 and a degree of alcoholysis of 99.1%, 1050ml of deionized water with a resistivity of 18.3MΩ·cm, 1.1g of sodium dodecyl sulfate, and a glass substrate with a size of 16cm×16cm and high flatness;

[0058] Solution preparation: PVA powder was added into deionized water at a rate of 1.2 g / min using a reactor equipped with a four-blade turbine stirring paddle and a heating device, with a stirring speed of 320 r / min. Stirring was continued for 32 minutes after adding the surfactant, and the solution was heated to 91°C for 1.1 hours.

[0059] Film preparation: The glass substrate was wiped clean with anhydrous ethanol and dried, and the prepared PVA solution was evenly coated on the clean substrate using a casting machine. The flow rate of the casting machine was controlled at 6 ml / min. The substrate coated with the PVA solution was placed in a drying oven. The temperature of the drying oven was set at 81°C. The drying time was 4.2 hours to form a PVA optical film. After drying, the PVA optical film was peeled off from the substrate;

[0060] Post-treatment: The prepared PVA optical film was annealed in an annealing furnace with the temperature set at 122°C for 2.2 hours. The annealed PVA optical film was surface treated with a plasma treatment device with the plasma treatment power set at 120 W for 35 minutes to obtain a high-transparency PVA optical film.

[0061] Example 6.

[0062] Material preparation: electronic balance with an accuracy of 0.01g, clean workbench, 125g of PVA powder with a degree of polymerization of 1950 and a degree of alcoholysis of 99.3%, 1250ml of deionized water with a resistivity of 18.7MΩ·cm, 1.3g of sodium dodecyl sulfate, and a stainless steel substrate with a size of 22cm×22cm and a surface roughness of 0.06μm;

[0063] Solution preparation: PVA powder was added into deionized water at a rate of 1.6 g / min using a reactor equipped with a four-blade turbine stirring paddle and a heating device, with a stirring speed of 360 r / min. Stirring was continued for 36 minutes after adding the surfactant, and the solution was heated to 93°C for 1.3 hours.

[0064] Film preparation: The glass substrate was wiped clean with anhydrous ethanol and dried, and the prepared PVA solution was evenly coated on the clean substrate using a scraper. The scraper angle of the scraper was adjusted to 40 degrees. The substrate coated with the PVA solution was placed in a drying oven. The temperature of the drying oven was set at 83°C. The drying time was 4.6 hours to form a PVA optical film. After drying, the PVA optical film was peeled off from the substrate.

[0065] Post-treatment: The prepared PVA optical film was annealed in an annealing furnace with the temperature set at 126°C for 2.6 hours. The annealed PVA optical film was surface treated using chemical vapor deposition equipment with the chemical vapor deposition temperature controlled at 170°C for 1.6 hours to obtain a high-transparency PVA optical film.

[0066] The high-transparency PVA optical films prepared in Examples 1-6 were tested according to the method in GB / T37384-2019;

[0067] 1. Appearance quality test: Under sufficient natural light or standard lighting conditions, place the film flat on a flat work surface, about 30 cm away from the eyes, and carefully observe the surface of the film visually to check for defects such as scratches, bubbles, impurities, etc., and observe the overall flatness of the film;

[0068] 2. Dimension deviation test: Use a micrometer or film thickness gauge with an accuracy of 0.01mm to randomly select at least five points at different locations of the film for measurement, calculate the average value of the measured values ​​as the actual thickness of the film, and compare it with the specified thickness to calculate the thickness deviation; use a steel ruler or tape measure with an accuracy of 1mm to measure the width and length of the film respectively, perform multiple measurements at different locations of the film, take the average value as the actual size, and compare it with the specified size to obtain the deviation;

[0069] 3. Optical performance test: Use a spectrophotometer to place the film sample in the test light path of the instrument, set a specific wavelength range, usually the visible light region (400nm-700nm), and measure the ratio of the light intensity passing through the film to the incident light intensity, which is the transmittance; use a haze meter for testing, place the film sample on the test bench of the instrument, ensure that the sample is flat and wrinkle-free, and the instrument emits specific light to illuminate the sample, measure the intensity of the scattered light and total transmitted light passing through the sample, and calculate the haze value;

[0070] 4. Mechanical properties test: Use a universal material testing machine to cut the film sample into a standard dumbbell-shaped specimen, install the specimen on the fixture of the testing machine, set the stretching speed to 5mm / min-10mm / min, start the testing machine, stretch the specimen, record the maximum tensile force when the specimen breaks, and calculate the tensile strength based on the cross-sectional area and maximum tensile force of the specimen; while conducting the tensile strength test, the testing machine automatically records the length change of the specimen during the stretching process, and the ratio of the elongation when the specimen breaks to the original length is the elongation at break;

[0071] 5. Thermal stability test: Place the film sample in a constant temperature box and set different temperature gradients, such as 50°C, 80°C, 100°C, etc. Keep it at each temperature for 2-4 hours, take out the sample, and observe the changes in the appearance of the film, such as whether there is deformation, discoloration, blistering, etc. At the same time, perform some performance tests again, such as light transmittance, tensile strength, etc., and compare them with the unheated samples to evaluate the thermal stability.

[0072] The PVA optical films prepared in Examples 1-6 have smooth surfaces, no obvious scratches, no bubbles, and no impurities, meet the requirements for appearance quality in the standard, show good thermal stability within the temperature range specified in the standard, and have no obvious deformation, discoloration, etc.; the high-transparency PVA optical film obtained in Example 1 has a thickness of 99.8 μm, a width and length deviation within ±0.5 mm, a light transmittance of 91%, a haze of 0.8%, a tensile strength of 105 MPa, and an elongation at break of 12%; the high-transparency PVA optical film obtained in Example 2 has a thickness of 119 μm, a width and length deviation within ±0.4 mm, a light transmittance of 90.5%, a haze of 0.7%, a tensile strength of 110 MPa, and an elongation at break of 11%; the high-transparency PVA optical film obtained in Example 3 has a thickness of 115 μm, a width and length deviation within ±0.3 mm, a light transmittance of 91%, a haze of 0.8%, a tensile strength of 110 MPa, and an elongation at break of 11%. The optical rate is 92%, the haze is 0.6%, the tensile strength is 115MPa, and the elongation at break is 13%; the high-transparency PVA optical film obtained in Example 4 has a thickness of 123μm, the width and length deviations are within ±0.4mm, the light transmittance is 91.5%, the haze is 0.7%, the tensile strength is 112MPa, and the elongation at break is 12.5%; the high-transparency PVA optical film obtained in Example 5 has a thickness of 108μm, the width and length deviations are within ±0.4mm, the light transmittance is 90.8%, the haze is 0.75%, the tensile strength is 108MPa, and the elongation at break is 11.5%; the high-transparency PVA optical film obtained in Example 6 has a thickness of 121μm, the width and length deviations are within ±0.3mm, the light transmittance is 91.2%, the haze is 0.65%, the tensile strength is 113MPa, and the elongation at break is 12.8%.

[0073] In addition to the above tests, the PVA optical films prepared in Examples 1-6 were also subjected to performance parameter tests, including acid and moisture tests, dissolution test and polymerization degree test:

[0074] Acid and moisture test: The acid content and moisture content in the film were tested using the acid-base titration method and the Karl Fischer moisture determination method. The acid content of the film prepared in Examples 1-6 was extremely low, all below 0.01%, and the moisture content was below 0.5%, which met the requirements of high-transparency optical films.

[0075] Dissolution test: The film was immersed in different solvents and its dissolution was observed. After testing, the film was almost insoluble in common organic solvents such as ethanol and acetone, and the dissolution rate in water was also very slow, indicating that the film has good solvent resistance;

[0076] Polymerization degree test: The polymerization degree of the film was determined by gel permeation chromatography (GPC). The test results showed that the polymerization degree of the film prepared in Examples 1-6 was between 1700 and 2000, which was basically consistent with the polymerization degree of the raw material, indicating that the polymerization degree of PVA did not change significantly during the preparation process.

[0077] By implementing the above-mentioned scheme, the PVA optical film prepared by the present invention meets the various indicators specified by the national standards in terms of appearance quality, dimensional deviation, optical properties, mechanical properties and thermal stability, and has low acid content, low moisture content, good solvent resistance, and high transparency with stable polymerization degree; these films are excellent in appearance without obvious flaws or defects; the dimensional deviation is controlled within a very small range to ensure the accuracy of the film; in terms of optical properties, the film has excellent light transmittance and low reflectivity, which can meet the needs of high-precision optical applications; in terms of mechanical properties, the film exhibits good tensile strength and toughness, and can withstand certain external forces without breaking; in terms of thermal stability, the film can maintain stable performance within a wide temperature range, and will not deform or degrade due to temperature changes; in addition, the preparation method involved in the present invention can stably produce high-quality high-transparency PVA optical films, showing extremely high reliability and practicality; the film has broad application prospects in multiple fields such as optics, electronics, and displays, and can meet the needs of different industries for high-transparency optical films, providing strong support for the development of related technologies.

[0078] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments. The above embodiments and descriptions are only preferred examples of the present invention and are not intended to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing a high-transparency PVA optical film, characterized in that: The method for preparing the high-transparency PVA optical film comprises the following steps: Step 1: prepare PVA powder, deionized water, surfactant and a clean substrate, and use deionized water as a solvent; Step 2: slowly add PVA powder into deionized water, stirring while adding to fully dissolve the PVA powder, add surfactant, continue stirring for a period of time to mix the solution evenly, and heat the solution at a certain temperature for a period of time; Step 3: uniformly coating the prepared PVA solution on a clean substrate by using a casting method or a doctor blade method, placing the substrate coated with the PVA solution in a drying oven, drying it at a certain temperature for a period of time to evaporate the solvent to form a PVA optical film, and peeling off the PVA optical film from the substrate after drying; Step 4: annealing the prepared PVA optical film, and performing surface treatment on the annealed PVA optical film to obtain a high-transparency PVA optical film.

2. The method for preparing a high-transparency PVA optical film according to claim 1, characterized in that: In step 1, the PVA powder has a polymerization degree of 1700-2000 and an alcoholysis degree of 99%-99.5%, the resistivity of the deionized water is greater than 18 MΩ·cm, and the surfactant is sodium dodecyl sulfate.

3. The method for preparing a high-transparency PVA optical film according to claim 1, characterized in that: In step 1, the substrate is a glass substrate or a stainless steel substrate. When the substrate is a stainless steel substrate, the surface roughness is less than 0.1 μm.

4. The method for preparing a high-transparency PVA optical film according to claim 1, characterized in that: The specific process of step 2 is: using a reactor equipped with a stirring paddle and a heating device, slowly add PVA powder to deionized water at a rate of 1-2 grams per minute, the stirring speed is 300-400r / min, and after adding the surfactant, continue stirring for 30-40 minutes. The solution heating temperature is 90-95°C and the heating time is 1-1.5 hours.

5. The method for preparing a high-transparency PVA optical film according to claim 1, characterized in that: When the casting method is adopted in step 3, the flow rate of the casting machine is 5-10 ml / min, and when the scraper coating method is adopted, the scraper angle is 30-45 degrees.

6. The method for preparing a high-transparency PVA optical film according to claim 1, characterized in that: In step 3, the substrate is wiped clean with anhydrous ethanol and dried before coating. The substrate coated with the PVA solution is placed in a drying oven with a temperature of 80-85° C. and a drying time of 4-5 hours.

7. The method for preparing a high-transparency PVA optical film according to claim 1, characterized in that: The specific process of step four is: the prepared PVA optical film is annealed in an annealing furnace at a temperature of 120-130°C for 2-3 hours, and the annealed PVA optical film is surface treated with plasma treatment equipment or chemical vapor deposition equipment to obtain a high-transparency PVA optical film.

8. The method for preparing a high-transparency PVA optical film according to claim 7, characterized in that: The annealed PVA optical film is surface treated by a plasma treatment device, wherein the power of the plasma treatment device is 100-200W and the treatment time is 30-60 minutes.

9. The method for preparing a high-transparency PVA optical film according to claim 7, characterized in that: The annealed PVA optical film is surface treated by chemical vapor deposition equipment, the deposition temperature is 150-200° C., and the deposition time is 1-2 hours.